Moonraker [compact disc, unabridged] - Fleming, Ian, 1908-1964 (Fleming, Ian, 1908-1964. James Bond books., 2000)
When James Bond is asked to settle a dispute involving the unimpeachable Sir Hugo Drax, head of the multimillion-dollar Moonraker missile program, he discovers a bizarre and terrifying truth about Drax and Moonraker that could prove fatal, not only for agent 007, but for millions.